IN VITRO ANTAGONISTIC ACTIVITIES OF INDONESIAN MARINE SPONGE AAPTOS AAPTOS AND CALLYSPONGIA PSEUDORETICULATA EXTRACTS AND THEIR TOXICITY AGAINST Vibrio spp. - Rosmiati Rosmiati; Habsah Mohamad; Tengku Sifzizul Tengku Muhammad; Najiah Musa; Aziz Ahmad; Noraznawati Ismail; Farida Mohamad; Nurhidayah Nurhidayah (Indonesian Aquaculture Journal, 2011)
Vibriosis is one of diseases which often results in mass mortality of Penaeus monodon larval rearing systems. It attacks shrimp of all stages in zoea, mysis and shrimp postlarva stage. This disease is caused by Vibrio spp, particularly Vibrio harveyi (a luminescent bacterium). Several kinds of antibiotics and chemical material have been used to overcome the disease but they have side effects to environment and human. The searching of bioactive compounds as an alternative treatment has been done for multi purposes. In this study diethyl eter, butanol and aqueous extract of Indonesian sponges Aaptos aaptos and Callyspongia pseudoreticulata were tested for in vitro activity against Vibrio spp. and Vibrio harveyi by using disc diffusion method. The result showed that all extracts of Aaptos aaptos gave a positive antibacterial activity towards those pathogenic bacteria. Meanwhile, only butanol extract of Callyspongia pseudoreticulata obtained to exhibit an antibacterial activity on those pathogenic bacteria. The strong anti-vibrio activity were shown by butanol and aqueous extract of Aaptos aaptos with the minimum inhibitory concentration (MIC) value of 0.313 and 0.625 mg/mL, respectively. Whilst, the butanol extract of Callyspongia pseudoreticulata indicated a low antibacterial activity with the MIC value of 10 mg/mL. Toxicity of those active extracts was evaluated by Brine Shrimp Lethality Test (BST). Interestingly, butanol and aqueous extracts of Aaptos aaptos did not show any toxic effect in Artemia salina larvae up to 8 x MIC (2.504 mg/mL and 5.000 mg/mL). It is the first report for the anti-vibr io activity of both Aaptos aaptos and Callyspongia pseudoreticulata. This results suggest that Aaptos aaptos has a potential to be used as a source of alternative compound to vibriosis prevention for mariculture.